Dinamika Model Matematika Reaksi T-Helper - Chilvia Tribhuana; Usman Pagalay; Elly Susanti (Jurnal Riset Mahasiswa Matematika, 2022)
T cells are a major component of the human immune system. These T cells have a number that varies depending on the body's immune response when fighting bacteria or viruses. However, the condition of excess immune cells in the body can also be dangerous. Theoretical studies on the dynamics of T-Helper cells in the body are needed to get the right simulation in treating patients without conducting medical tests on every patient on a daily basis. This study discusses the dynamics of the mathematical model of the T-Helper reaction with the influence of antigen and IL-2. From this study, two equilibrium points were obtained, namely disease-free equilibrium and endemic equilibrium. The use of parameter values from the experimental results shows that the disease-free equilibrium point is locally unstable, while the endemic equilibrium point is locally stable. The numerical simulation showed that the antigen increased from 1st day to the highest value at 0.926 on the 11th day until on the 20th day it started to be constant towards at the value  which is the antigen could be activate the resting T-Helper. The process of activating T-Helper, create IL-2 which can stimulating the proliferation and activity of T-Helper cells, so they can divide the activated cell of T-Helper into two memory cells.